PROFIL MAHASISWA YANG MEMILIKI DAN TIDAK MEMILIKI PRESTASI OLAHRAGA DALAM MENENTUKAN KEINGINAN MOTIVASI YANG DOMINAN (STUDI PADA MAHASISWA JURUSAN PENDIDIKAN OLAHRAGA ANGKATAN 2009) - SUTRISNO, TRI (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract In teaching and learning processmotivation is an important part, because motivation will make someone have more spirit in order to reach his objective. Therefore, Students of Sport Education Department Sport Science Faculty Unesa must have strong motivation. Motivation can appear from many thing, one of them is achievement. Sport Education Department students are students who have ability in certain sport and some of them have sport achievements. Hopefully, this achievements can increase motivation to study to get the better result. This phenomenon was used to conduct a research about the profileof students who have and do not have sport achievement in determining the passion of dominant motivation. A questionnaire was used to rank students motivation. There are 28 students who have Sport achievement and 28 students who do not have it used as the research sample. Based on the research result of students who have Sport achievement, there is 60,7% of them want to be a sport teacher; 17,9% of them want to learn sport; 10,7 of them want to be a police officer or army; 3,6 of them want to be an athlete; 3,6% of them want to play outside; 3,6% of them like the excitement. While the result of students who do not  have sport achievement shows that there is 67,9% of them want to be a sport teacher; 7,1%  of them want to learn sport; 3,6% of them want to be an athlete; 3,6% of them want to be a police officer or army; 3,6% of them want to improve health; 3,6% of them want to be a coach; 3,6% of them want to be an entrepreneur in sport; 3,6% of them love to makes friend; and 3,6% want to have good shape of body. It can be concluded that there is not significant difference in motivation of choosing Sport Education Department between students who have sport achievement and do not have it. Keywords: Motivation, Student who have achievement and do not have achievement.